Outcomes and endpoints in cancer trials: bridging the divide. Issue 1 (January 2015) - Wilson, Michelle K; Collyar, Deborah; Chingos, Diana T; Friedlander, Michael; Ho, Tony W; Karakasis, Katherine; Kaye, Stan; Parmar, Mahesh K B; Sydes, Matthew R; Tannock, Ian F; Oza, Amit M
Summary: Cancer is not one disease. Outcomes and endpoints in trials should incorporate the therapeutic modality and cancer type because these factors affect clinician and patient expectations. In this Review, we discuss how to: define the importance of endpoints; make endpoints understandable to patients; improve the use of patient-reported outcomes; advance endpoints to parallel changes in trial design and therapeutic interventions; and integrate these improvements into trials and practice. Endpoints need to reflect benefit to patients, and show that changes in tumour size either in absolute terms (response and progression) or relative to control (progression) are clinically relevant. Improvements in trial design should be accompanied by improvements in available endpoints. Stakeholders need to come together to determine the best approach for research that ensures accountability and optimises the use of available resources.